Heterogeneity of Reporting Outcomes in the Spine Surgery Literature. Issue 4 (May 2018) - Cooper, Maxwell E.; Torre-Healy, Luke A.; Alentado, Vincent J.; Cho, Samuel; Steinmetz, Michael P.; Benzel, Edward C.; Mroz, Thomas E.
Abstract : Study Design: Review of spine surgery literature between 2005 and 2014 to assess the reporting of patient outcomes by determining the variability of use of patient outcomes metrics in the following categories: pain and disability, patient satisfaction, readmission, and depression. Objective: Expose the heterogeneity of outcomes reporting and discuss current initiatives to create more homogenous outcomes databases. Summary of Background Data: There has been a recent focus on the reporting of quality metrics associated with spine surgery outcomes. However, little consensus exists on the optimal metrics that should be used to measure spine surgery outcomes. Materials and Methods: A PubMed search of all spine surgery manuscripts from January 2005 through December 2014 was performed. Linear regression analyses were performed on individual metrics as well as outcomes categories as a fraction of total papers reviewing surgical outcomes. Results: Outcomes reporting has increased significantly between January 1, 2005 and December 31, 2014 [175/2871 (6.1%) vs. 764/5603 (13.6%), respectively; P <0.001; R 2 =98.1%]. For the category of pain and disability reporting, Visual Analog Score demonstrated a statistically significant decrease in use from 2005 through 2014 [56/76 (73.7%) vs. 300/520 (57.7%), respectively; P <0.001], whereas Oswestry Disability Index increased significantly in use [19/76 (25.0%) vs. 182/520 (35.0%), respectively; P <0.001]. For quality of life, EuroQOL-5 Dimensions increased significantly in use between 2005 and 2014 [4/23 (17.4%) vs. 30/87 (34.5%), respectively; P <0.01]. In contrast, use of 36 Item Short Form Survey significantly decreased [19/23 (82.6%) vs. 57/87 (65.5%), respectively; P <0.01]. For depression, only the Zung Depression Scale underwent a significant increase in usage between 2005 and 2014 [0/0 (0%) vs. 7/13 (53.8%), respectively; P <0.01]. Conclusions: Although spine surgery outcome reporting has increased significantly over the past 10 years, there remains considerable heterogeneity in regards to individual outcomes metrics utilized. This heterogeneity makes it difficult to compare outcomes across studies and to accurately extrapolate outcomes to clinical practice.